The immortal mind : science and the continuity of consciousness beyond the brain - Laszlo, Ervin, 1932-; Peake, Anthony (Rochester, Vermont : Inner Traditions, 2014)
"Scientific evidence for the continual presence of consciousness with or without connection to a living organism"--
Bestaat er zoiets als een bewustzijn dat, losgekoppeld van een fysieke vorm, constant aanwezig is in het heelal?
Includes bibliographical references (pages 155-162) and index.
Keywords: Consciousness; Philosophy of mind